Prevalence of brucellosis in livestock of African and Asian continents: A systematic review and meta-analysis - Suresh, Kuralayanapalya P.; Patil, Sharanagouda S.; Nayak, Akshata; Dhanze, Himani; Rajamani, Shinduja; Shivamallu, Chandan; Cull, Charley A.; Amachawadi, Raghavendra G. (Frontiers in Veterinary Science, 2022)
Brucellosis is an important endemic zoonotic disease in most Asian and African countries. Brucellosis is a highly contagious bacterial disease that mainly affects ruminants, but it may affect equines, canines, and felines. The disease is of utmost significance from an economic standpoint in countries where there is no national brucellosis prevention and eradication policy in operation. Hence, information about disease burden, incidence, prevalence, and geographical distribution play a critical role in planning appropriate intervention strategies for the control and prevention of Brucellosis. Research articles that were published during the period 2000-2020 were considered for this study after reinforced scrutiny by two independent authors. Heterogeneity was analyzed using meta-regression, while subgroup and sensitivity analysis was performed to estimate the residual heterogeneity and pooled prevalence of Brucellosis in livestock. Univariate meta-regression revealed that confounders such as region, a test of diagnosis, and species had the highest R2 values of 17.8, 8.8, and 2.3% respectively, which suggests the presence of heterogeneity leading to further investigation on sensitivity and subgroup analysis. The combined pooled prevalence of brucellosis in both Asia and African countries was estimated as 8%. The pooled prevalence of brucellosis in the Indian livestock population was estimated to be 12%. The findings of our systematic review and meta-analysis indicate that brucellosis continues to be an important animal and public health concern in developing countries of Asia and Africa, as evidenced by the prevalence rate of brucellosis in these regions. Our findings suggested that well-planned surveillance studies in different geographic settings are needed to generate reliable data on disease burden including the economic loss in Asian and African countries.